Analysis of The Volatility and Asymmetric Stocks Information in The Energy Sector on The Indonesia Stock Exchange 2021-2024 - Tuti Kusmini; Buddi Wibowo (Eduvest - Journal of Universal Studies, 2025)
Introduction/Main Objectives: This paper examines the relationship between market uncertainty and asymmetric information in the Indonesian energy sector from 2021 to 2024, using the World Uncertainty Index (WUI) as a measure of global economic and political uncertainty. Background Problems: The study is driven by heightened uncertainty due to major global events such as the COVID-19 pandemic and the Russia-Ukraine conflict, which have introduced significant volatility into the market. Novelty: This research uniquely focuses on the Indonesian energy sector, an underexplored area in global finance, and uses the World Uncertainty Index (WUI) to link global uncertainties with the performance of Indonesia's developing energy market. Research Methods: Employing a regression model, the study investigates the causal relationship between stock market volatility and asymmetric information. Results: The findings reveal that increased volatility negatively impacts market efficiency, indicating that uncertainty and information gaps hinder the market’s ability to fully reflect available information. Conclusion: the study highlights the significant impact of market uncertainty and asymmetric information on stock market volatility and efficiency in Indonesia’s energy sector, offering valuable insights for improving investment strategies and policy formulation in a volatile global environment